1903 Or. Spec. Laws 34, An Act to incorporate the city of Portland, ch. 3, art. 4, § 73, pt. 56. - (:unkn) unknown (My University, 1903)
To prohibit the carrying of deadly or dangerous weapons in a concealed manner
Keywords: CARRY - CONCEALED